Liver Transplantation in the Adult following Kasai Operation in Infancy. (July 2018) - Gerlach, Undine; Roberts, Keith; Abradelo, Manuel; Mergental, Hynek; Isaac, John; Muiesan, Paolo; Mirza, Darius; Perera, Thamara
Abstract : Abstract: Liver transplantation (LT) is indicated as a late life-saving operation for a proportion of patients undergone Kasai procedure. Technical aspects of LT operations could be a challenge due due to adhesion formation over many years that later become vascularised from portal hypertension, and secondary sclerosing cholangitis. Furthermore, surgical aspects of the childhood operation are often unknown, in historical cases and may only be revealed in the course of transplantation. In a retrospective study we assessed all adult liver transplant recipients in our centre following Kasai operation. Patient and graft characteristics were collected as well as the technical details of the Kasai operation and liver transplantation. We analysed patient and graft survival with regards to the surgical challenges and posttransplant complications in this cohort of late failing Kasai patients. Eleven adult patients (6 female, 5 male; mean age 33.2 ± 11.4) with previous Kasai operations underwent liver transplantation in our centre. Kasai operations had been carried out within the first 3 months postnatal and were fashioned as choledochoduodenostomy (n=3) or hepaticojejunostomy (n=3). In 5 cases the technical details of the operation remained unknown. The main reason for Kasai failure and indication for liver transplantation was either secondary sclerosing cholangitis (n=8), portal hypertension (n=2) or both (n=1). A whole liver graft was implanted in 9 and a right liver split graft in 2 patients. The majority were DBD grafts (n=8), there was one DCD and one living donor as well as one domino graft. All transplantations were carried out as end-to-side hepaticojejunostomies. Two patients underwent retransplantation 9 days and 6.3 years after the first transplantation, 3 patients died. Adult liver transplantation after Kasai operation can be a technical challenge but remains the only therapeutical option for these patients. Envisioning the potential risks and pitfalls may be crucial to guarantee further longterm survival and an adequate quality of life in this particular group of patients.